2001
DOI: 10.1542/peds.108.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Antibiotic Use in Children: A Randomized Trial in 12 Practices

Abstract: A limited simultaneous educational outreach intervention for parents and providers reduced antibiotic use among children in primary care practices, even in the setting of substantial secular trends toward decreased prescribing. Future efforts to promote judicious prescribing should continue to build on growing public awareness of antibiotic overuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
194
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(207 citation statements)
references
References 32 publications
8
194
2
3
Order By: Relevance
“…In human research, the link between heavy drinking occasions during pregnancy and the risk of FAS is well established 65, 66, 67, 68, 69, 70. For low amounts of alcohol (8–28 g per occasion), several studies have found that there is no increased risk of behavioural and/or developmental deficits in children 69, 71, 72, 73.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human research, the link between heavy drinking occasions during pregnancy and the risk of FAS is well established 65, 66, 67, 68, 69, 70. For low amounts of alcohol (8–28 g per occasion), several studies have found that there is no increased risk of behavioural and/or developmental deficits in children 69, 71, 72, 73.…”
Section: Resultsmentioning
confidence: 99%
“…For low amounts of alcohol (8–28 g per occasion), several studies have found that there is no increased risk of behavioural and/or developmental deficits in children 69, 71, 72, 73. However, there is some evidence that the consumption of 42–56 g per week during pregnancy may have adverse effects on neurodevelopment 70. To date, however, there are no longitudinal human studies that have followed alcohol‐exposed individuals over a sufficient amount of time and used FASD diagnostic criteria to establish the relationship between dose and/or pattern of alcohol intake during pregnancy and FASD.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with others that have demonstrated a relationship between education and more judicious use of antibiotics for pediatric upper respiratory illnesses. [34][35][36] Patient asthma education is increasingly being viewed as an important marker of quality of care in the ambulatory care setting. 37 The results from this finding suggest other potential benefits for asthma education, as it seems to be associated with more judicious use of antibiotics by providers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported greater magnitudes of effect of interventions on physician practices. 16,17 These studies may have engaged practices that were most receptive to change in this area and may be less generalizable to community-level approaches for this and other public health problems. True community-level interventions to promote judicious antibiotic use have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is clear to many that interventions to reduce unnecessary prescribing will require community-level intervention that simultaneously targets all sources of perceived demand for unnecessary antibiotic use, as well as changing the supply side: physician prescribing behavior. 14,15 Among the diverse attempts to intervene in this area have been interventions in specific health care delivery systems 16,17 or for particular conditions, such as otitis media in children 18 and bronchitis in adults. 17 The Centers for Disease Control and Prevention (CDC) have implemented national efforts to address antibiotic overuse through education of providers, 7 as well as campaigns to change the knowledge and attitudes of the public about the harms of antibiotic overuse.…”
mentioning
confidence: 99%